Indigenous Medicinal Plants as Biofilm Inhibitors for the Mitigation of Antimicrobial Resistance - Elikplim Kwesi Ampofo; Isaac Kingsley Amponsah; Evelyn Asante-Kwatia; Francis Ackah Armah; Philip Kobla Atchoglo; Abraham Yeboah Mensah (Advances in Pharmacological and Pharmaceutical Sciences)
The majority of indigenes in the rural areas of Ghana use herbal medicines for their primary health care. In this study, an ethnobotanical survey was undertaken to document medicinal plants used by traditional healers in the Ejisu-Juaben district in the Ashanti region of Ghana to treat infections and to further investigate the antibiofilm formation properties of selected plants in resisting pathogenic bacteria. Seventy medicinal plants used by traditional practitioners for the treatment of skin infections and wounds were documented from the ethnobotanical survey. Forty out of the seventy plants were collected and their methanol extracts evaluated for antimicrobial activity by the agar diffusion assay. Extracts that showed antibacterial activity were tested for biofilm inhibitory activity, and the most active plant was subsequently purified to obtain the active constituents. Biofilm formation was significantly mitigated by petroleum ether, ethyl acetate, and methanol extracts of Holarrhena floribunda stem bark. Bioassay-guided fractionation of an alkaloidal extract prepared from the methanol fraction led to the isolation of three steroidal alkaloids, namely, holonamine, holadienine, and conessine. The isolated compounds demonstrated varying degrees of biofilm formation inhibitory properties. The current study reveals that screening of indigenous medicinal plants could unravel potential leads to salvage the declining efficacy of conventional antibiotics. Holarrhena floribunda stem bark extract has strong biofilm formation inhibition properties, which could be attributed to the presence of steroidal alkaloids.